The association between magnesium levels and gout: evidence from Mendelian randomization, a Chinese cross-sectional study, and NHANES analysis - Jiao, Congcong; Shao, Yang; Zhao, Yuxin; Feng, Ruichao; Cui, Xiangfei; Luan, Junjun; Hao, Xiangnan; Ma, Cong; Feng, Haoshen; Yang, Xu; Zhou, Hua (Frontiers in Nutrition, 2025)
IntroductionAlthough the roles of micronutrients in human health are widely acknowledged, their specific associations with gout remain inadequately explored. This study integrates evidence from Mendelian randomization (MR), Chinese cross-sectional, and NHANES analyses to comprehensively investigate.MethodsThe MR analysis was used to evaluate the potential causal associations between 15 trace elements (copper, calcium, iron, magnesium, potassium, selenium, zinc, carotenoids, folate, vitamin A, vitamin B12, vitamin B6, vitamin C, vitamin D, and vitamin E) and gout risk from the FinnGen database (n = 327,457). Significant findings were validated via logistic regression in Chinese clinical data (n = 4,359) and NHANES 2011-2018 data (n = 13,902).ResultsUnivariable MR identified calcium, magnesium, and vitamin B6 as associated with gout. Multivariable MR indicated that only higher magnesium levels causally reduced gout risk (OR = 0.630, 95% CI: 0.400-0.992, p = 0.046). Consistently, high serum magnesium (Q4) was associated with lower gout risk in the Chinese clinical data (OR = 0.546, 95% CI: 0.319–0.933, p = 0.027) versus the lowest quartile (Q1). NHANES analysis confirmed that higher dietary magnesium intake lowered gout risk (OR = 0.738, 95% CI: 0.550–0.989, p = 0.049). Additionally, the restricted cubic spline (RCS) found that the OR began below 1 when the dietary magnesium intake exceeded 0.27 g/day.DiscussionThis multifaceted study provides novel evidence supporting a protective role of magnesium against gout. The underlying mechanism may involve magnesium’s influence on uric acid or its anti-inflammatory effects. These hypotheses need to be clarified by further experimental and clinical studies.